A Taxonomy-Based Approach Towards NUI Interaction Design - Klompmaker, Florian; Paelke, Volker; Fischer, Holger Gerhard

A Crook is a Crook … But is He Still a Crook Abroad? - On the Effect of Immigration on Destination-Country Corruption - Dimant, Eugen; Krieger, Tim; Redlin, Margarete

A crook is a crook ... but is he still a crook abroad? On the effect of immigration on destination-country corruption - Dimant, Eugen; Krieger, Tim; Redlin, Margarete

Musical Variants in Encoding, Analysis and Visualization - Kepper, Johannes; Roland, Perry; Röwenstrunk, Daniel (Balisage: The Markup Conference 2013)

Bildung für nachhaltige Entwicklung. Den Alltag gestalten – Teilhabe ermöglichen. Verbraucherbildung als Aufgabe von Schule - Oepping, Anke; Schlegel-Matthies, Kirsten (Schule NRW. Amtsblatt des Ministeriums für Schule und Weiterbildung)

Ethik, Konsumentenverantwortung und Verbraucherbildung im Spannungsfeld - Schlegel-Matthies, Kirsten (Haushalt in Bildung und Forschung (HiBiFo))

Fachliche Betreuung des Schwerpunktthemas: Ethik – Konsum – Verbraucherbildung. - Schlegel-Matthies, Kirsten (Haushalt in Bildung und Forschung (HiBiFo))

Ernährungs- und Verbraucherbildung im Unterricht - Oepping, Anke; Schlegel-Matthies, Kirsten

Business Model Representations: A Cross-Disciplinary Review of the Pragmatic, Semantic and Syntactic Foundations of Existing Approaches - John, Thomas; Kundisch, Dennis (Pre-ECIS Workshop on the Digitization in Business Models and Entrepreneurship (DiBME))

A Review of the Effects of Lunch: On Adults’ Short-term Cognitive Functioning - Müller, Katrin; Libuda, Lars; Terschlüsen, Anna Maria; Kersting, Mathilde (Canadian Journal of Dietetic Practice and Research)
Because of widespread irregular lunch consumption by both children and adults, information on the effects of lunch on short-term cognitive functioning is relevant to public health. In September 2012, a MEDLINE search was conducted for studies in which the effects of lunch on cognitive performance were examined. Eleven experimental studies published from 1981 to 1996 were found and evaluated; all involved adults. In three studies, the effects of lunch and lunch skipping were compared; the remaining studies involved a determination of the effects of lunch size and lunch composition. Results of studies in which lunch was compared with no lunch indicate that lunch leads to potential impairment of some aspects of cognitive functioning in the early afternoon. Lunch size may influence cognitive functioning, with impairment more likely to occur after a large lunch than a small lunch. Furthermore, in comparison with low-fat lunches, high-fat lunches seem to result in slower but more accurate responses to some cognitive tasks. However, these suggestions must be viewed with caution, as they are based on only a few studies and are not thoroughly supported by high-quality evidence. In addition, results obtained with adults are not applicable to children. Thus, the potential effects of lunch need further examination in children and adults.

Do Non-Monetary Incentive Systems Matter? Evidence From the Restructuring of a Non-Monetary Incentive System in an Online Community - Mutter, Tobias (Proceedings of the 21st European Conference on Information Systems (ECIS))

Towards an Agile Simulation-based Method for Creating, Evaluating and Selecting Business Models - John, Thomas; Weskamp, Christoph; Kundisch, Dennis; Suhl, Leena (Pre-ECIS Workshop on the Digitization in Business Models and Entrepreneurship (DiBME))

Designing a Web-Based Classroom Response System - Kundisch, Dennis; Herrmann, Philipp; Whittaker, Michael; Neumann, Jürgen; Magenheim, J.; Reinhardt, W.; Beutner, Marc; Zoyke, A. (Proceedings of the Design Science Research in Information Systems and Technologies 2013 (DESRIST))

Does it Pay Off to Bid Aggressively? An Empirical Study - Herrmann, Philipp; Kundisch, Dennis; Rahman, Mohammad (Proceedings of the 46th Hawaii International Conference on System Sciences (HICCS))

Rekrutierung von Müttern mit Säuglingen in einer Interventionsstudie – erste Erkenntnisse aus der PINGU-Studie. - Mesch, C.; Stimming, M.; Wagner, A.; Libuda, Lars; Kersting, M. (Ernährungsumschau International)

Verfahrenstechnische Entwicklung zum Hinterspritzen von Echtholzfurnieren mit Wood-Plastic-Composites (WPC) - Schröder , Cathrin

Untersuchung des Prozessverhaltens neuartiger Einzugzonen-Konzepte für Kautschukextruder - Hallmann, Tobias

Prospective association of protein intake during puberty with body composition in young adulthood - Assmann, K.E.; Joslowski, G.; Buyken, Anette; Cheng, G.; Remer, T.; Kroke, A.; Günther, A.L.B. (Obesity)

Breastfeeding and Its Prospective Association with Components of the GH-IGF-Axis, Insulin Resistance and Body Adiposity Measures in Young Adulthood – Insights from Linear and Quantile Regression Analysis - Günther, Anke L. B.; Walz, Helena; Kroke, Anja; Wudy, Stefan A.; Riedel, Christina; von Kries, Rüdiger; Joslowski, Gesa; Remer, Thomas; Cheng, Guo; Buyken, Anette (PLoS ONE)

Adapting Hardware Systems by Means of Multi-Objective Evolution - Kaufmann, Paul
Reconfigurable circuit devices have opened up a fundamentally new way of creating adaptable systems. Combined with artificial evolution, reconfigurable circuits allow an elegant adaptation approach to compensating for changes in the distribution of input data, computational resource errors, and variations in resource requirements. Referred to as ``Evolvable Hardware'' (EHW), this paradigm has yielded astonishing results for traditional engineering challenges and has discovered intriguing design principles, which have not yet been seen in conventional engineering. In this thesis, we present new and fundamental work on Evolvable Hardware motivated by the insight that Evolvable Hardware needs to compensate for events with different change rates. To solve the challenge of different adaptation speeds, we propose a unified adaptation approach based on multi-objective evolution, evolving and propagating candidate solutions that are diverse in objectives that may experience radical changes. Focusing on algorithmic aspects, we enable Cartesian Genetic Programming (CGP) model, which we are using to encode Boolean circuits, for multi-objective optimization by introducing a meaningful recombination operator. We improve the scalability of CGP by objectives scaling, periodization of local- and global-search algorithms, and the automatic acquisition and reuse of subfunctions using age- and cone-based techniques. We validate our methods on the applications of adaptation of hardware classifiers to resource changes, recognition of muscular signals for prosthesis control and optimization of processor caches.